THE IMPACT OF TRANSLATION TECHNIQUES ON ASSERTIVE SPEECH ACT OF INEZ PRODUCT PAKAGING - Rois, Amadea Anna; Kirana, Alvina Janice; Setyowati, Lilis; Arum, Siska Dewi (Kajian Linguistik dan Sastra, 2020)
This article aims to: 1) find the translation techniques used by translators in translating assertive speech acts in Inez product packaging, 2) finding the speech act shifts, 3) knowing the impact of translation techniques on the quality of translations. The method used in this research is a descriptive qualitative research method. The data source of this research is product packaging and translation. The data is in the form of informational text in the Inez packaging and translation. We found seven speech act shifts from ten data related to assertive speech acts. In addition, the translators use nine translation techniques when translating.Keywords: Translation technique, assertive, shifting, quality